Chloromethane Degradation in Soils: A Combined Microbial and Two‐Dimensional Stable Isotope Approach. Issue 2 (1st March 2018) - Jaeger, Nicole; Besaury, Ludovic; Kröber, Eileen; Delort, Anne‐Marie; Greule, Markus; Lenhart, Katharina; Nadalig, Thierry; Vuilleumier, Stéphane; Amato, Pierre; Kolb, Steffen; Bringel, Françoise; Keppler, Frank
Abstract : Chloromethane (CH3 Cl, methyl chloride) is the most abundant volatile halocarbon in the atmosphere and involved in stratospheric ozone depletion. The global CH3 Cl budget, and especially the CH3 Cl sink from microbial degradation in soil, still involves large uncertainties. These may potentially be resolved by a combination of stable isotope analysis and bacterial diversity studies. We determined the stable isotope fractionation of CH3 Cl hydrogen and carbon and investigated bacterial diversity during CH3 Cl degradation in three soils with different properties (forest, grassland, and agricultural soils) and at different temperatures and headspace mixing ratios of CH3 Cl. The extent of chloromethane degradation decreased in the order forest > grassland > agricultural soil. Rates ranged from 0.7 to 2.5 μg g −1 dry wt. d −1 for forest soil, from 0.1 to 0.9 μg g −1 dry wt. d −1 for grassland soil, and from 0.1 to 0.4 μg g −1 dry wt. d −1 for agricultural soil and increased with increasing temperature and CH3 Cl supplementation. The measured mean stable hydrogen enrichment factor of CH3 Cl of −50 ± 13‰ was unaffected by temperature, mixing ratio, or soil type. In contrast, the stable carbon enrichment factor depended on CH3 Cl degradation rates and ranged from −38 to −11‰. Bacterial community composition correlated with soil properties was independent from CH3 Cl degradation or isotope enrichment. Nevertheless, increased abundance after CH3 Cl incubation was observed in 21 bacterial operational taxonomical units (OTUs at the 97% 16S RNA sequence identity level). This suggests that some of these bacterial taxa, although not previously associated with CH3 Cl degradation, may play a role in the microbial CH3 Cl sink in soil. Core Ideas: Chloromethane biodegradation is affected by temperature and soil properties. The stable carbon enrichment factor of CH3 Cl strongly depends on CH3 Cl consumption. The overall bacterial community is unaffected by chloromethane degradation. Unexpected bacterial taxa displayed increased abundance upon CH3 Cl incubation.